The surveillance of birth defects: the usefulness of the revised US standard birth certificate. - Watkins, M L (1996)
To assess the sensitivity and positive predictive value of birth defects reported on the 1989 revision of the US Standard Birth Certificate, a population of 76,862 Atlanta-area births during 1989 and 1990 was used as the basis for comparing 771 birth certificates that reported birth defects with 2428 live-born infant records in a birth defects registry that uses multiple sources of case ascertainment. Only 14% of birth defects in the registry records were reported on birth certificates. After the analysis was restricted to defects recognizable at birth, the sensitivity and positive predictive value of the birth certificates were 28% and 77%, respectively. Birth certificates underestimate birth defect rates and should be used cautiously for birth defect surveillance and epidemiological studies.